Pengaruh Struktur Kepemilikan Terhadap Manajemen Laba dan Dampaknya Terhadap Nilai Perusahaan - Rita Tri Yusnita (JURNAL EKONOMI PERJUANGAN, 2019)
This study aims to determine the effect of simultaneous and partial ownership structure and earnings management on firm value in the Consumer Goods Industry Sector Companies that are listed on the Indonesia Stock Exchange in 2014. The method used in this study is the census method. The population studied was 32 companies in the Consumer Goods Industry Sector that were listed on the Indonesia Stock Exchange in 2014. The data collected were secondary data. Analysis of the data in this study used path analysis using SPSS V. 24. The results showed that the ownership structure and earnings management, simultaneously, had a significant effect on the value of the company in the Consumer Goods Industry Sector Companies that were listed on the Indonesia Stock Exchange in 2014. The ownership structure, partially, has no significant effect on the value of the company in the Consumer Goods Industry Sector Companies listed on the Indonesia Stock Exchange in 2014. Earnings management, partially, has a significant effect on the firm value of the Consumer Goods Industry Sector Companies that are listed on the Exchange Indonesian Securities in 2014, and ownership structure does not significantly influence earnings management in the Consumer Goods Industry Sector Companies that are listed on the Indonesia Stock Exchange in 2014.Â Keywords: ownership structure, earnings management, company value